Makna dan Nilai-Nilai Pendidikan Akhlak pada Puisi Piatu Karya F. Aziz Manna - Kodrat Eko Putro Setiawan; Wahyuningsih Wahyuningsih; Devi Cintia Kasimbara (Education & Learning, 2021)
Understanding the meaning in a poem requires a theory. The object of this research is the poem Piatu by F. Aziz Manna. The theory used in this research is Michael Riffaterre's semiotics. The purpose of this research is to understand the meaning of poetry through heuristic reading, hermeneutic reading, models, matrices, and variants as well as moral education values. The method in this research is descriptive qualitative. The result of this research is the heuristic reading in the poem entitled Piatu, there are eight stanzas that produce the meaning of the poem based on language convention, not yet at the meaning. In the hermeneutic reading in the poem entitled Piatu, there are eight stanzas which in total contain the meaning of the longing of a child (immature) who does not have a mother anymore because he has passed away. This longing is a manifestation of a child's love and affection for his mother. This love and affection made him stronger and more willing to accept all the conditions given by Allah. The model in this poem is the Orphan. The matrix is ??a child whose mother has abandoned because of her death. The variants in this poem include: I don't cry or laugh; Flowers that embrace twigs; this solitude is strange. The values ??of moral education are respect for mothers and the command to love orphans.